The relationship between fossomatic somatic cell counts and milk yield, butterfat, protein and lactose production in various fractions of dairy milk - Conradie, J. G.(Jacob Gerhardus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1985.